Building the "Smart Village" Through the implementation of the Non-Formal Education to Improve English Language Skills In the village of Geluran Taman Sidoarjo" - Ani Faujiah (EDUCATIO : Journal of Education, 2018)
The role of the learning education is an undertaking in the process of educating the nation Participated as a real work in the form of donations of educational development (Act No. 20 of 2003). Education has a very important function in developing the relationship between education and the realities of life steady and meaningful in the life of society, whereas the fundamental role of education for humanizing. Education organized by course institutions can Contribute to the nation's education as non-formal education (Act 13 paragraph 1 No. 20 of 2003). Non-formal education can play a role as a complement (complement) to formal education, non-formal education that is Able to present subjects or learning activities that have not been included in the formal education curriculum. Implementation of English is an attempt to teach learners in mastering the English (Degeng, 1990). This implies that in learning English have opted activities, define, and develop methods or strategies are optimal to Achieve the desired results. English speaking skills require knowledge of spelling, grammar, vocabulary, and culture (Bowen et al, 1985, Finocchiaro and Bonomo, 1973). The early English course is to meet the needs of learners in mastering the knowledge and skills of the English so as to answer and respond to the user's environment services (Krakower, 1985). This research concerns the role of English course in the development of public education Geluran Taman Sidoarjo. This study took place in SMART EDUCATION Geluran Park course in Sidoarjo, the which is an English course that has characteristics that attract. The focus of this research are: (1) The community in Geluran village (2) Motivation Learners Attend courses SMART EDUCATION.